Penggunaan Digital Accounting dan Dampaknya terhadap Pengelolaan Keuangan dan Peningkatan Usaha Pelaku Usaha Mikro di Kota Kendari - Abhiyoga Seto Kusumo; Sodik; Indah Dewi Nurhayati (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to understand the use of digital accounting applications by micro-entrepreneurs in Kendari City and its impact on their financial management and business improvement. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving business owners who hold Business Identification Numbers (NIB) and utilize digital applications such as Si Apik, BukuWarung, Beecloud, and Jurnal by Mekari. The findings reveal that digital accounting facilitates transaction recording, financial reporting, and raises awareness of the importance of financial management. Despite challenges such as internet connectivity, limited device capacity, and low digital literacy, most business owners showed improvements in cash flow recording and decision-making. The use of digital accounting supports the transition from manual bookkeeping to a more efficient and transparent digital system.